Is Traditional Media Still Relevant in English Language Teaching?: Perceptions and Challenges - Gema Febriansyah; Muhammad Zaim; Harris Effendi Thahar (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The relevance of traditional media in English Language Teaching (ELT) has come under increasing scrutiny due to the proliferation of digital technologies. This study aims to investigate whether traditional media still hold relevance in the modern ELT classroom, amidst widespread adoption of digital tools. Employing a mixed-methods approach, the research integrates quantitative surveys of 100 students and qualitative interviews with five English lecturers at Padang State Polytechnic, Indonesia. The survey results indicate varied perceptions: while traditional media are valued for their structured and reliable content, they lack the interactivity and engagement offered by digital media. Findings reveal that 65% of students find digital media easier to understand, and 70% prefer digital tools over traditional resources. Interviews with lecturers highlight the necessity of a balanced, blended approach that integrates both traditional and digital media to enhance learning outcomes and cater to diverse student needs. The study concludes that a blended approach is optimal, combining the stability and reliability of traditional resources with the dynamic, engaging capabilities of digital tools. The implications of this study underscore the importance of digital literacy training for educators and suggest future research should focus on the long-term effects of blended learning, addressing accessibility and equity issues in digital media use.